Efektivitas Pendekatan Contextual Teaching and Learning (CTL) dalam Pembelajaran Materi Akidah Akhlak pada Siswa - A. Faizul Mubarak; Aminoto, Imam Mahdi (Indonesian Journal of Action Research, 2026)
Purpose – This study aims to examine the effectiveness of the contextual learning approach in Aqidah Akhlak learning to improve students’ conceptual understanding and moral behavior among tenth-grade students at Madrasah Aliyah Nurul Yaqin. The study is motivated by the dominance of conventional teaching methods, particularly lectures, which tend to emphasize theoretical understanding of moral values without optimal implementation in students’ daily lives. This condition can be seen in the low level of discipline, limited politeness, and weak sense of responsibility among students during the learning process. Design – This study employed a qualitative case study design involving teachers, the head of the madrasah, and students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. Findings – The findings indicate that the contextual learning approach has significant potential in reinforcing the internalization of Aqidah Akhlak values among students. However, the successful implementation of this approach depends on several supporting factors, including teachers’ pedagogical readiness, the availability of contextual learning resources, and continuous evaluation practices. This study enriches the discourse of Islamic education by emphasizing that contextual learning does not merely enhance students’ cognitive comprehension, but also encourages the formation of moral attitudes and behaviors that are relevant to contemporary social and digital challenges.